Understanding of Nanofiber Face Mask as Corona Virus Disease Prevention in Human - Tofan Agung Eka Prasetya; Indiah Ratna Dewi; Muhamad Rifki Taufik; Khandaker Fadwana Islam (Health Dynamics, 2024)
Background: Corona virus has become a global issue. It makes various countries have taken this outbreak very seriously. One of the necessary precautions is by using a face mask. The nanofiber technology on face masks greatly helps the public and government to increase the prevention of disease spread. The purpose of this study was to conduct a systematic literature review on nanofiber face masks as human corona virus disease prevention. Methods: Stages of systematic literature review of 632 documents was carried out using text mining techniques, while hierarchical cluster analysis were carried out for the extraction of terms in documents. Results: The terms "mask" and "nanofiber" were the most words that appear (more than 40 times) in the WoS and PubMed nanofiber mask document form. On the other hand, the terms "disease" and "respiration" mostly appeared in human corona virus disease prevention. Both of these terms were used to obtain specific articles as a basis for the study of nanofiber mask as human corona disease prevention. Conclusion: This study is very important since prevention measures against corona disease (corvid-19) are a very high concern. The next study is expected to bring this review literature into an experimental study of nanofiber applied to face masks.